Bullying and Its Treatment in the Prophetic Hadiths - ALMOMANI, NEDAL HASAN FALAH (Journal of Ecohumanism, 2025)
This study aims to demonstrate bullying and its treatment in the Prophetic hadiths, and the importance of treating bullying using various methods related to religion and faith. The researcher used the inductive and analytical approach to explain the nature of bullying and its treatment in the Prophetic hadiths. The study concluded that there are several types of bullying, its causes, and its treatment in a practical way through the authentic Prophetic hadiths that are applicable to all times. The study also recommended following the Prophetic hadiths as they contain many treatments for bullying